Green spaces, blue spaces and human health: an updated umbrella review of epidemiological meta-analyses - Wang, XiaoWen; Feng, Bowen; Wang, Juan (Frontiers in Public Health, 2025)
IntroductionGreen spaces have been recognized for their ecological services, including air purification and biodiversity protection, which contribute to the enhancement of life quality and well-being. However, despite the surge in research evaluating the impact of blue-green spaces on health outcomes, we still lack a definitive understanding of how green and blue spaces affect human health outcomes. To assess the impact of blue-green spaces on human health outcomes, we systematically summarized and evaluated the relationship between green and blue spaces and human health through an umbrella review of epidemiological meta-analyses up to the year 2024.MethodsThe study follows the PRISMA guidelines and includes meta analyses from PubMed, Embase, and Cochrane databases, focusing on evidence and methodological improvements. Inclusion criteria encompass studies on human populations, exposure to green and blue spaces, and health outcomes such as mortality, disease risk, and physiological indicators. Data extraction and quality assessment of evidence and methods are conducted using the GRADE system and AMSTAR 2 tool.ResultsWe find that green space exposure is associated with reduced all-cause mortality, mortality from cardiovascular diseases, incidence of diabetes and metabolic syndrome, low birth weight, and mental health improvements. Blue spaces also show positive associations with beneficial health outcomes, including reduced obesity rates and improved psychological well-being. However, the evidence regarding green space exposure and specific health outcomes such as cancer, asthma, and allergic rhinitis remains heterogeneous and unclear.DiscussionGreen and blue spaces clearly have some impact on health. For some outcomes, the effects are robust. This article emphasizes the importance of improving residents’ health through urban planning in public health strategies.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier [CRD42024533346].